2012
DOI: 10.3109/0886022x.2012.676526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Birth Weight on Impaired Renal Development and Function and Hypertension in Rat Model

Abstract: These data showed that abnormal kidney development and renal dysfunction occurred in LBW rats due to a maternal low-protein diet. Possessing a decreased glomerular number might be a risk factor for hypertension in LBW rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 28 publications
5
24
0
Order By: Relevance
“…Several epidemiological studies closely linked IUGR to adult onset diseases such as hypertension [1][2][3][4].Our previous rats study showed that low birth weight offspring of maternal protein restriction diet exposure decreased glomerular number and impaired renal function, and caused hypertension from postnatal 2 months old [5]. However, the basic mechanism that IUGR offspring led to later renal dysfunction was not fully uncovered.…”
Section: Effect Of Folic Acid Supplementation On Renal Phenotype and mentioning
confidence: 97%
See 2 more Smart Citations
“…Several epidemiological studies closely linked IUGR to adult onset diseases such as hypertension [1][2][3][4].Our previous rats study showed that low birth weight offspring of maternal protein restriction diet exposure decreased glomerular number and impaired renal function, and caused hypertension from postnatal 2 months old [5]. However, the basic mechanism that IUGR offspring led to later renal dysfunction was not fully uncovered.…”
Section: Effect Of Folic Acid Supplementation On Renal Phenotype and mentioning
confidence: 97%
“…the composition of diet was described in our previous study [5]. The animals were allowed free access to water and feed.…”
Section: Rats and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were housed in a room with temperature of 21-22˚C, humidity of 50-70% and a 12 h light/dark cycle. The composition of the diet was as previously described (14). There were 8-10 offspring in each nest during lactation, and nests with >14 offspring or <8 offspring were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Pregnant rats were randomly divided into a control group (CON), an IUGR group (IUGR) and an L-Arg group (LA). The establishment of the IUGR model was conducted as described in our previous studies with modifications (14,15). The pregnant rats in the CON group were fed a 21% protein diet (normal feed) and normal water during pregnancy and lactation.…”
Section: Methodsmentioning
confidence: 99%